New Challenges and Opportunities for Opioid Agonist Treatment Access and Retention: A Scoping Review - Power, Niamh (Journal of drug issues, 2026)
Changes to the landscape of opioid use have occurred throughout the past two decades. Opioid agonist treatment (OAT) plays an important role in reducing opioid-related harms. Yet, people with opioid use disorder (PWOUD) face issues with access and retention. This scoping review sought to provide an up-to-date synthesis on barriers and facilitators to OAT. Ninety-three studies were included. Major barriers included cost, waiting lists, and negative public attitudes toward treatment. Prominent facilitators included OAT education and flexible treatment conditions such as telehealth-delivered OAT. In prison settings, limited support with treatment referral was a barrier. Fear of judgement was a challenge for pregnant people. There was a lack of information on barriers and facilitators specific to PWOUD dealing with chronic pain or mental health comorbidities. Results highlight new challenges in reaching an increasingly heterogeneous PWOUD population. Findings underline the potential for recent advancements in treatment modalities to promote access and retention.